Goods Robots Based On Color Using Microcontroller Atmega 328 - Novi Rahayu; Ade Titin Sumarni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
Robot is an electrical or electronic mechanical device that works automatically that can work alone without outside control. By using robots in production activities, the process will be more efficient and effective. In this study, robots are made using a microcontroller as a robot controller and color detector to separate goods based on color. Color sensor is useful for getting color data. The detected color consists of Red, Green, Blue, all colors are processed in a microcontroller that functions as the brain in the robot that is made.